Perbandingan Hasil Creatinin Clirens Test (CCT) dan Estimasi Laju Filtrasi Glomerulus (eLFG) Pada Pasien Kemoterapi di Rumah Sakit Prima Medika - Wijayanti, Sariati; Putra, I Gusti Putu Agus Ferry Sutrisna; Juliantara, I K. Putra (Bali International Scientific Forum, 2020)
Background: Creatin clirens test (CCT) is a reliable examination to estimate LFG. To solve some weaknesses in the creatinine clirens test, we can use estimation of glomerulus filtration rate (eLFG). Estimation of glomerulus filtration rate (eLFG) can be used as the Cockcroft Gault (CG) formula, Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI). Each formula has advantages and disadvantages. Objective: The aim of this study was to compare the results of CCT with eLFG (CG, MDRD, CKD-EPI) and the correlation between results of CCT and eLFG (CG, MDRD, CKD-EPI). Method: Research on the comparison of the results of creatinine clarity test (CCT) and estimation of glomerulus filtration rate (eLFG) is a type of comparative analytical study with a retrospective approach. Result: The results showed that there were no differences in the results of CCT and eLFG (CG, MDRD, CKD-EPI) (p > 0.05). In addition, there is correlation between CCT and eLFG (CG, MDRD, CKD-EPI) (r > 0.05). Conclusion: It can be concluded that there is no difference in the results of CCT and eLFG (CG, MDRD, CKD-EPI). In addition, there is a correlation between the results of CCT and eLFG (CG, MDRD, CKD-EPI).